Incipient dynamic recrystallization and adiabatic shear bands in Ti–7Al studied via in situ X-ray diffraction. (June 2021) - Magagnosc, D.J.; Lloyd, J.T.; Meredith, C.S.; Pilchak, A.L.; Schuster, B.E.
Abstract: The interconnected phenomena of dynamic recrystallization (DRX) and adiabatic shear bands (ASBs) are critical features of dynamic deformation and fracture in metals. Despite their importance, observations of these phenomena have largely been restricted to post-mortem analyses. Here we report on the first in situ X-ray diffraction (XRD) observations of DRX. By combining high strain rate loading via Kolsky bar with high speed X-ray diffraction, time resolved observations of microstructural evolution in Ti–7Al are made. XRD measurements are coupled with explicit finite element simulations to assess the stress, strain, and temperature dependence of the microstructural evolution. These observations reveal a continuous evolution of the microstructure with increasing plastic strain up to a maximum stress. At the maximum stress, the structure ceases evolving and the subsequent softening suggests the onset of shear banding. As a whole, these unique experiments definitively reveal the onset of DRX to be driven by accumulation of plastic strain and not the temperature rise associated with plastic deformation. The observed sequence of events further suggests DRX results in microstructural softening and precedes ASB formation. Highlights: Novel in situ X-ray diffraction experiments are used to examine structural evolution during high strain rate loading. Finite element simulations are used to fit experimental loading curves and determine stress, strain, and temperature. Combining in situ diffraction and FEM simulations reveals the onset of dynamic recrystallization shortly after yield. Dynamic recrystallization is found to depend only on the accumulated plastic strain and not the associated temperature rise.